PENGARUH MODEL PEMBELAJARAN CONCEPTUAL UNDERSTANDING PROCEDURES (CUPs) BERBANTUAN MEDIA HANDOUT TERHADAP KEMAMPUAN PEMAHAMAN KONSEP DITINJAU DARI GAYA BELAJAR DI SMK N 3 PEKALONGAN - Farah Salsabila (Delta: Jurnal Ilmiah Pendidikan Matematika, 2019)
The objectivives of this research were to investigate the influence of learning model CUPs used handouts of the ability of understanding the concept in terms of learning style in SMK N  3 Pekalongan. This is a quantitative research with the quasi experiment. Its population was all of the students of X TT SMK N 3 Pekalongan consisting of 6 class. The samples of the research were taken by using the cluster random sampling.The result of this research are: 1). CUPs Learning model used handouts as a media  produced the ability of understanding the concept better than learning model directly. 2). The students with visual learning style is ability to create understanding comprehension concept rather than the students with auditory and kinesthetic learning style, 3). The students with a kinesthetic learning style have the same ability to create concept understanding comprehension is the same used CUPs or direct learning, the students with a visual learning style produced a better ability in learning CUPs than direct learning, and students with the auditory ability produced a better understanding in learning CUPs than learning directly. 4). In learning model CUPs used handouts as a media, the ability of understanding the concept of students in a study visual as good as auditory, the ability of understanding the concept of students with study visual style and auditory better than kinesthetic. 5) in direct learning model, the ability of understanding the concept of students who have style visual and auditory style are the same, the ability of understanding the concept of students learn auditory as good as kinesthetic, and the ability of understanding the concept of students in a study visual better than kinesthetic.